This preview shows pages 1–3. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: HOMEWORK ASSIGNMENT 8 PHYS852 Quantum Mechanics II, Spring 2008 New topics covered: Scattering amplitude, crosssection, partial wave expansion . 1. Spherical Bessel functions: The spherical Bessel function j ( ) is defined as j ( ) = ( 1) parenleftbigg 1 d d parenrightbigg sin . Show that this state satisfies the radial wave equation. Answer: Let j ( ) = ( 1) u ( ) / , where u ( ) = +1 parenleftbigg 1 d d parenrightbigg sin The radial wave equation for u ( ) is then bracketleftbigg d 2 d 2 ( + 1) 2 + 1 bracketrightbigg u ( ) = 0 Let H = bracketleftbigg d 2 d 2 ( + 1) 2 + 1 bracketrightbigg Strategy: We will show that if we assume H u = 0 then we must also have H +1 u +1 = 0. Then if we establish that H u = 0, then H u = 0 for all . First we derive the recursion relation: u +1 = +2 parenleftbigg 1 d d parenrightbigg +1 sin = +2 parenleftbigg 1 d d parenrightbigg 1 +1 parenleftbigg 1 d d parenrightbigg sin = +2 parenleftbigg 1 d d parenrightbigg 1 u Let A = +2 parenleftbigg 1 d d parenrightbigg 1 = bracketleftbigg d d ( + 1) bracketrightbigg Then we have u +1 = Au . Now we want to compute the commutator [ H ,A ] = H A = AH . First computing H A , we find bracketleftbigg d 2 d 2 ( + 1) 2 + 1 bracketrightbiggbracketleftbigg d d ( + 1) bracketrightbigg = d 3 d 3 + ( 2 + 2)( + 1) 3 + (2 )( + 1) 2 d d ( + 1) d 2 d 2 d d + ( + 1) 1 Similarly, for AH we find bracketleftbigg d d ( + 1) bracketrightbiggbracketleftbigg d 2 d 2 ( + 1) 2 + 1 bracketrightbigg = d 3 d 2 ( + 1) 2 d d + (2 + 1)( + 1) 3 + d d ( + 1) d 2 d 2 ( + 1) . Subtracting the two gives H A AH = 2( + 1) 2 d d 2( + 1) 2 2 = 2 2( + 1) 2 bracketleftbigg d d ( + 1) bracketrightbigg = 2( + 1) 2 A. Starting from H A = AH + 2( +1) 2 A , we operate on u and use H u = 0 to find H u +1 = 2( + 1) 2 u +1 which gives bracketleftbigg H 2( + 1) 2 bracketrightbigg u +2 = 0 , But we see that H 2( + 1) 2 = d 2 d 2 ( + 1) 2 + 1 2( + 1) 2 = d 2 d 2 ( + 1)( + 2) 2 + 1 = H +1 Thus we have proven that H +1 u +1 = 0 under the assumption H u = 0 ....
View
Full
Document
This note was uploaded on 11/26/2010 for the course PHYSICS PHYS 852 taught by Professor Michaelmoore during the Spring '10 term at Michigan State University.
 Spring '10
 MichaelMoore
 mechanics, Work

Click to edit the document details